Policy of the soviet government in Uzbekistan in the 20-30s of the XX century towards the representatives of the education system - Hoshimov Soibjon Abdurazzakovich (Genius Journals, 2022)
The article describes the policy of brutal repression of the Soviet government in the 20s and 30s of the last centuries against the representatives of the education system of Uzbekistan on the basis of primary sources.
Keywords: education; enlightenment; cultural revolution; class enemy